2020
DOI: 10.46662/jass-vol7-iss2-2020(185-198)
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Employee Training, Employee Empowerment, Team Work With Job Satisfaction

Abstract: Current research is designed to check the impact of employee training, employee empowerment, team work on job satisfaction. Employee training, employee empowerment, team work are independent variables and job satisfaction is dependent variable. Overall, 160 employees of banks employees who are working at managerial level are selected randomly. Results indicates that employee training, employee empowerment, team work has significant positive impact on job satisfaction. It is also seen that teamwork is emerging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Our empirical findings showed that employee empowerment has a mediating role between organizational learning, employee training and job satisfaction with employee performance. This finding is compatible with various studies that link organizational learning with employee empowerment (Choi, 2020); employee training with employee empowerment (Khaliq et al ., 2020); job satisfaction with employee empowerment (Zembylas and Papanastasiou, 2005). However, (Salahat, 2021b; Seo and Lee, 2016) conceptualize the mediation role of employee empowerment between work environment and employee performance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our empirical findings showed that employee empowerment has a mediating role between organizational learning, employee training and job satisfaction with employee performance. This finding is compatible with various studies that link organizational learning with employee empowerment (Choi, 2020); employee training with employee empowerment (Khaliq et al ., 2020); job satisfaction with employee empowerment (Zembylas and Papanastasiou, 2005). However, (Salahat, 2021b; Seo and Lee, 2016) conceptualize the mediation role of employee empowerment between work environment and employee performance.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, training enhances the organizational ability toward positive change; well-trained employees know when and where to use their knowledge and skills (Panagiotakopoulos, 2020). According to the literature review, employee training affects employee engagement (Sendawula et al, 2018) and employee empowerment (Khaliq et al, 2020) positively and significantly. Drawing from the preceding discussion and aligning it with the Resource-Based View theory's perspective on employee training (Yin et al, 2019), we formulate the following hypotheses for the current study.…”
Section: Literature Review 21 Review Of Knowledge Framework: a Biblio...mentioning
confidence: 99%
“…On the other hand, new methods of teamwork emerge with factors that seek change and are more adaptable, finding teams with different reactions, interpretations and behaviors (Kerrissey et al 2020). For Alvi et al (2020), what is fundamental for teams is the satisfaction they feel, the training and learning on the job, the empowerment and the rewards received. Among the factors that influence employees and work teams, Sailer et al (2021) address one that has not been analyzed very much; it is the place and spaces of work and the distribution of offices or desks that have been highlighted, where access to colleagues, cohesion, the distribution of information, the perception of productivity, the state of concentration and others are involved.…”
Section: Teamworkmentioning
confidence: 99%
“…Ethics is a broad theme that coexists everywhere in life and in the business and administration, and which proves to be essential in all areas, including leadership (Bauman 2018;Kalshoven and Taylor 2018), teamwork (Alvi et al 2020;Lyubovnikova et al 2018), effective communication (Alyammahi et al 2020;Touhidul and Sorooshian 2019) and productivity (Ebert and Freibichler 2017;Tammany et al 2019). Therefore, this current research-which possesses a high degree of novelty while compared with other studies on similar topics, can be regarded as crucial given its main focus and, also, based on the research gap that was successfully identified, namely: the opportunity to describe the implication of ethics in leadership, teamwork, effective communication, and productivity, which includes the application of ethical values as university graduates assume the role of each of the mentioned dimensions of study in the organizations.…”
Section: Introductionmentioning
confidence: 99%
“…With the increased attention to human resources in the organization, the emphasis was laid on ensuring employee stability and fostering searches for employee turnover retention. Scientists admit that employee turnover management is a complex phenomenon covering the following aspects: the creation of a favourable psychological and microclimate in the organization (Bufquin, DiPietro, Partlow, 2018), encouraging teamwork (Alvi, Kayani, Mir, 2020), ensuring the quality of relationships between colleagues and the manager and its feedback (Krywalski, 2020), ensuring respect and recognition of employees and evaluation of their efforts, (Čuček and Kač, 2020;Zhu et al, 2017) providing their support (de la Torre-Ruiz, Vidal-Salazar, Cordón-Pozo, 2019;Alam et al, 2020) and improving motivation methods (Fletcher, Carter, Lyubovnikova, 2018;Navickas et al, 2023;Awais Bhatti and Alnehabi, 2023).…”
Section: Introductionmentioning
confidence: 99%